Queer Shakespeare (Bloomsbury Publishing (UK), 2026)
The go-to resource for understanding desire, same-sex and trans eroticism in Shakespeare's texts, as well as in stage performance and in textual criticism, this open access second edition features revisions to the original chapters and an additional 5 new chapters. The plays and poems of Shakespeare overflow with sexual and erotic discourses, languages, and representations concerning eroticism and sex, and they display forms of embodiment that intersect with the erotic. This preoccupation with sex and desire often disrupts on page and stage the otherwise heavily regulated worlds of sexuality and desire in Shakespeare’s society. The updated chapters take stock of the ideas and arguments explored in queer Shakespeare scholarship since the first edition in 2017. Five new chapters expand the scope of the book and trace further lines of enquiry: queerness in stage performance, and in the original intersection between textual and trans analysis; queerness and race; queerness and critical disability studies in the narrative poetry, and trans theory of queer Shakespeare. Together with a new introduction, Queer Shakespeare expands the possibilities for teaching both Shakespeare and queer theory in all of its manifestations. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the Bloomsbury Open Collections Library Collective.